KELAYAKAN BOOKLET SUBMATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN DENGAN PENGAYAAN TRANSPIRASI ENAM TANAMAN DIKOTIL - Lara Klarisya; Entin Daningsih; Reni Marlina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the feasibility of the booklet submaterial of structure and function of plant tissue with additional information about transpiration which was used as a learning media. The research method was descriptive. The media was validated for instrument which was used to validate the booklet media. The instrument validators consisted of two Biology Education lecturers and one high school biology teacher. The booklet media validators consisted of two Biology Education lecturers and three high school biology teachers who conducted the 2013 curriculum. The data were analyzed using Lawshe method. The results of the booklet media validation analysis obtained CVR and CVI average of 0.99 classified as valid. Therefore, the booklet media was feasible to be used in the learning process for the structure and function of plant tissue in high school. Keywords: Booklet, feasibility, validation.